Mixed bacterial culture mediated direct conversion of bio-glycerol to diols - Parate, Roopa; Mane, Rasika; Dharne, Mahesh; Rode, Chandrashekhar (Bioresource Technology, 2018)
Direct and economic transformation of biodiesel derived crude glycerol is gaining more significance. During screening of bacterial cultures Klebsiella pneumoniae and Enterobacter aerogenes were able to convert crude bio-glycerol to 2,3-butanediol (2,3-BDO) and 1,3-propanediol (1,3-PDO), as major compounds, ethanol and acetoin as minor compounds, with a conversion of 69% and 79% respectively. Process optimization could achieve maximum conversion at pH 7.0, 37 degrees C, 30-40 g/L glycerol and 1.5 g of inoculum until 120 h. Mixed cultures led to complete glycerol conversion with optimal yield and productivity. An innovative approach of using crude glycerol for sustained growth and tolerance of bacteria as source of carbon and energy makes this study more significant. In addition to this, a mixed culture concept introduced here is expected to make impact in process economics for industrial scale synthesis for direct transformation of glycerol into C3 and specifically, C4 diols.
Keywords: 1; 2; 3-Butanediol; 3-Propanediol; Bioconversion; Bioglycerol; Mixed culture